2005
DOI: 10.1021/es050316c
|View full text |Cite
|
Sign up to set email alerts
|

Power Generation in Fed-Batch Microbial Fuel Cells as a Function of Ionic Strength, Temperature, and Reactor Configuration

Abstract: Power density, electrode potential, coulombic efficiency, and energy recovery in single-chamber microbial fuel cells (MFCs) were examined as a function of solution ionic strength, electrode spacing and composition, and temperature. Increasing the solution ionic strength from 100 to 400 mM by adding NaCl increased power output from 720 to 1330 mW/m2. Power generation was also increased from 720 to 1210 mW/m2 by decreasing the distance between the anode and cathode from 4to 2 cm. The power increases due to ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
432
6
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 858 publications
(471 citation statements)
references
References 20 publications
26
432
6
7
Order By: Relevance
“…These proved that MFCs had great potential to be applied in removing carbon and nitrogen from wastewater. However, there are also several drawbacks that block the application of MFCs: (1) the anaerobic conditions in the anode chamber inhibit the contaminant removal, which prefers aerobic conditions (Kelly and He, 2014); (2) significant pH drift occurs in the electrode-biofilm, due to the generation and consumption of protons by the oxidation of carbon and the denitrification of nitrate, respectively (Cheng et al, 2012); (3) poor efficiency of electron transfer, at both the anode and cathode (Pham et al, 2009); (4) high overpotential loss and poor electricity productivity Hamelers et al, 2010); (5) the volume of MFC reactors in most studies is limited to a small scale due to the poor electricity generation (Cheng et al, 2012;Kondaveeti and Min, 2013;Liu et al, 2005;Puig et al, 2011;Van Doan et al, 2013), so that it is crucial to solve the problem of reactor scale-up for further application of the technology.…”
Section: Simultaneous Carbon and Nitrogen Removal Using Mfcsmentioning
confidence: 99%
“…These proved that MFCs had great potential to be applied in removing carbon and nitrogen from wastewater. However, there are also several drawbacks that block the application of MFCs: (1) the anaerobic conditions in the anode chamber inhibit the contaminant removal, which prefers aerobic conditions (Kelly and He, 2014); (2) significant pH drift occurs in the electrode-biofilm, due to the generation and consumption of protons by the oxidation of carbon and the denitrification of nitrate, respectively (Cheng et al, 2012); (3) poor efficiency of electron transfer, at both the anode and cathode (Pham et al, 2009); (4) high overpotential loss and poor electricity productivity Hamelers et al, 2010); (5) the volume of MFC reactors in most studies is limited to a small scale due to the poor electricity generation (Cheng et al, 2012;Kondaveeti and Min, 2013;Liu et al, 2005;Puig et al, 2011;Van Doan et al, 2013), so that it is crucial to solve the problem of reactor scale-up for further application of the technology.…”
Section: Simultaneous Carbon and Nitrogen Removal Using Mfcsmentioning
confidence: 99%
“…While 3D anodes improve MFC performance due to increased active surface area for biofilm growth, it was demonstrated that increasing the distance between cathode and anode decreases the MEC efficiency (Ghangrekar and Shinde, 2007;Liu et al, 2005a). This dependence is related to an increased resistance to proton transport with increasing distance (Gil et al, 2003).…”
Section: The Effect Of Anode Thickness On Hydrogen Productionmentioning
confidence: 99%
“…The hydrogen evolution reaction often limits the overall MEC performance and cathodes with a larger surface area have demonstrated an increase in hydrogen production and current density (Call et al, 2009). Also, both MFC and MEC tests have demonstrated that the maximum power output can be increased by reducing the distance between the electrodes (Ghangrekar and Shinde, 2007;Liu et al, 2005a;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of temperature on acetate fed reactors offer insights into electrogenesis only; they have typically found that the maximum power output drops at lower temperatures [10][11][12][13][14][15]. Cheng et al [12] and Lu et al [14] found convincing linear relationships (R 2 N 0.99) between temperature (from 4 to 30°C) and performance: about 33 mW/m 2 /°C and 4 A/m 3 /°C implying Q 10 temperature coefficient values for electrogenesis of 1.5 and 2.0 for power and current respectively.…”
Section: Introductionmentioning
confidence: 99%